The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1136/bmjoq-2017-000207
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the informational needs of patients with IPF and their caregivers: ‘You get diagnosed, and you ask this question right away, what does this mean?’

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive, incurable lung disease whose intrusive symptoms rob patients of their quality of life. Patients with IPF rely on their caregivers for support and assistance in amounts that vary according to patients’ individual circumstances and disease severity. Knowledgeable and well-informed patients and caregivers are best suited to deal with life-altering conditions like IPF.MethodsWe conducted two hour-long focus groups with 13 patients with IPF and 4 careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 13 publications
(12 reference statements)
1
59
0
Order By: Relevance
“…Many participants in this study expressed a desire to know what the future would hold for them. The importance of understanding prognosis, on an individual level rather than a group average, also emerged in our previous qualitative research and that of others . However, it contrasts with another recent qualitative study where many were ambivalent about receiving information about disease progression .…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Many participants in this study expressed a desire to know what the future would hold for them. The importance of understanding prognosis, on an individual level rather than a group average, also emerged in our previous qualitative research and that of others . However, it contrasts with another recent qualitative study where many were ambivalent about receiving information about disease progression .…”
Section: Discussionmentioning
confidence: 49%
“…The importance of understanding prognosis, on an individual level rather than a group average, also emerged in our previous qualitative research 16 and that of others. 17 However, it contrasts with another recent qualitative study where many were ambivalent about receiving information about disease progression. 18 Other authors have reported that carers were more likely than patients to seek frank information about prognosis, especially if the patient was deteriorating.…”
Section: Discussionmentioning
confidence: 80%
“…PROMs alone will not lead to improved outcomes without a change in clinicians' approach to care. Ramadurai et al 58 explored the education and information gaps and described both disease-specific as well as individualized content for both patients and caregivers: Education is key because it increases understanding, sense of control, and empowerment. Such information needs to be delivered at the first visit and revisited throughout the course of the disease.…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%
“…Poor perceived and worsened QoL (physical, psychosocial, emotional, spiritual, and existential needs) 27,58 Lack of: 1) whole person approach; 2) standardized approach to needs assessment; 3) time to properly assess these needs Provide strategies to preserve QoL Provide anticipatory guidance, use of symptom action plans. Educational resources for patients and caregiver K-BILD, 38 ATAQ-IPFca, 37 SGRQ-IPF, 36 L-IPF, 39 NAT: PD-interstitial lung disease 56 27,75,76 Lack of: 1) PC approach and delayed referral; 2) clinical guidelines; 3) training in sensitive, patient-centered communication Implement end-to-end patient-centered care models Adopt early advanced care planning Provide education and support to the MDT NAT: PD-interstitial lung disease 56 (for palliative care needs), MSAS, 82 MYMOP, 57 L-IPF, 39 K-B interstitial lung disease (to assess QoL and quality of dying), 38 IPF-PREM (to assess care delivery processes) Caregiver distress and increased burden 27 Lack of: 1) understanding of the caregiver needs and engagement; 2) anticipatory guidance;…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%
“…In an interesting paradox, some caregivers, for the first time in the course of their loved-one’s disease, perceive themselves as truly useful at this transition: instead of just being a ‘nag’, caregivers can give physical care—helping with the logistics of O 2 and taking on more household duties. 9 …”
Section: When O 2 Is Needed At Restmentioning
confidence: 99%